2015
DOI: 10.2217/mmt.15.5
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene-Directed Small Molecule Inhibitors for the Treatment of Cutaneous Melanoma

Abstract: Achievements in cancer genetics and molecular biology have revolutionized the treatment options available for advanced melanoma. Patients with certain molecularly defined melanomas have been the most fortunate beneficiaries of recently US FDA-approved therapies that target aberrant MAPK pathway signaling, yet response rates and duration of response remain suboptimal. Furthermore, many patients harbor melanomas for which no approved targeted therapies currently exist. Since the approval of vemurafenib, a select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 110 publications
(148 reference statements)
0
1
0
Order By: Relevance
“…In about 90% of PDAC cases, K-Ras is mutated and the mutated K-Ras drives tumorigenic signaling cascades [ 20 ]. Thus, most efforts have been directed to inhibit the action of oncogenes [ 21 , 22 , 23 , 24 ], for instance, the development of selective K-Ras inhibitors [ 25 ]. In some of the recent studies, however, the other side of the oncogene actions has been revealed [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In about 90% of PDAC cases, K-Ras is mutated and the mutated K-Ras drives tumorigenic signaling cascades [ 20 ]. Thus, most efforts have been directed to inhibit the action of oncogenes [ 21 , 22 , 23 , 24 ], for instance, the development of selective K-Ras inhibitors [ 25 ]. In some of the recent studies, however, the other side of the oncogene actions has been revealed [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%